ChemInform Abstract: Fast, Solvent‐Free, Highly Enantioselective Three‐Component Coupling of Aldehydes, Alkynes, and Amines Catalyzed by the Copper(II)pybox Complex under High‐Vibration Ball‐Milling. Issue 33 (August 2015) - Li, Zhenhua; Jiang, Zhijiang; Su, Weike
Abstract The employed copper(II) pybox catalyst system can be easily recovered and reused five times maintaining high performance without additional replenishment of ligands.